2023
DOI: 10.3390/w15142581
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Urban Stream Flooding with Machine Learning, LiDAR, and 3D Modeling

Abstract: Flooding in urban streams can occur suddenly and cause major environmental and infrastructure destruction. Due to the high amounts of impervious surfaces in urban watersheds, runoff from precipitation events can cause a rapid increase in stream water levels, leading to flooding. With increasing urbanization, it is critical to understand how urban stream channels will respond to precipitation events to prevent catastrophic flooding. This study uses the Prophet time series machine learning algorithm to forecast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…Xiao et al [54] found that Prophet improved runoff modeling in the Zhou River Basin. Bolick et al [55] used the Prophet method to predict hourly water level changes in an urban stream (South Carolina, USA) and obtained very accurate estimates, with coefficient of determination values greater than 0.9.…”
Section: Discussionmentioning
confidence: 99%
“…Xiao et al [54] found that Prophet improved runoff modeling in the Zhou River Basin. Bolick et al [55] used the Prophet method to predict hourly water level changes in an urban stream (South Carolina, USA) and obtained very accurate estimates, with coefficient of determination values greater than 0.9.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Bolick et al used the Prophet time series machine learning algorithm to predict the hourly water level variations at certain sites in urban streams. They further gathered ground optical remote sensing (lidar) data for Hunnicutt Creek, modeling these regions in 3D to elucidate how the predicted water level changes correspond to the variations in water levels within the stream channel [38]. A more comprehensive overview on the recent applications of radar data in rainfall prediction and real-time forecasting systems can be found in [39].…”
Section: Discussionmentioning
confidence: 99%
“…This study uses the Prophet time series machine learning algorithm to forecast hourly changes in water level in an urban stream, Hunnicutt Creek, Clemson, South Carolina (SC), USA. Bolick et al [3] collected terrestrial Light Detection and Ranging (LiDAR) data for Hunnicutt Creek to model these areas in 3D to illustrate how the predicted changes in water levels correspond to changes in water levels in the stream channel [3].…”
mentioning
confidence: 99%